Blue Economy, Challenges and Multilateral Cooperation in African Coastal Countries - (:unkn) unknown (My University, 2022)
The oceans represent seventy-one percent of the earth’s surface. There are plenty of resources in the coastal and oceanic environment, and which is the potential “new fuel” for the future economy growth in the coastal nations. The international organizations such as the FAO, OCED, World Bank as well as some NGOs interested to push forward the marine nations to accelerate marine economy development. In recent decade, the marine economy or blue economy is the highlighting field interested by the public, the government and the researchers.In 2010, a famous book titled of The blue economy: 10 years, 100 innovations, 100 million jobs highlighted the concerns on the blue economy throughout the world (Pauli, 2010). Africa is a huge continent with long coastline. Development is the key task for the governments of African countries. To find the new sector of economic growth will accelerate the GDP increase and job position enlargement. In the year of 2015, the Agenda 2063 what we want popular version published by African Union, the marine economy/blue economy was regarded as the new engine for African economy growth in the future (AU, 2015).In Africa continent, thirty-eight of the fifty-four countries are coastal states with more than 90 percent of Africa’s imports and exports transported by sea. Marine space under Africa’s jurisdiction totalled about 13 million square kilometers. Marine fishery makes a vital contribution to the food security and nutrition supply for over 200 million Africans in coastal states. If fully exploited and well managed, Africa’s blue economy can therefore constitute a major source of wealth and sustainable development for the whole continent. The Blue Economy Policy Handbook for Africa produced by ECAs sub-regional Office in East Africa in 2015, was a contribution to helping the African coastal nations benefit from what the African Union call the "New Frontier of African Renaissance".No doubt that the blue economy is the
Keywords: African Research